2018
DOI: 10.1016/j.mce.2017.11.002
|View full text |Cite
|
Sign up to set email alerts
|

The effect of ovarian reserve and receptor signalling on granulosa cell apoptosis during human follicle development

Abstract: The poor oocyte quality in older women has previously been linked to the depletion of the ovarian reserve of primordial follicles and an increase in granulosal apoptosis. Granulosa cells were collected from 198 follicles and individually analysed by flow cytometry. In the young IVF patients, the level of apoptosis was inversely proportional to the expression of bone morphogenetic protein (BMPR1B) and follicle stimulating hormone (FSH) receptors. Conversely, in the older patients this relationship became dysreg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0
2

Year Published

2018
2018
2021
2021

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 37 publications
(30 citation statements)
references
References 68 publications
(73 reference statements)
0
27
0
2
Order By: Relevance
“…However, a recent flow cytometry study with selective gating of pure mural GCs (identified by the expression of FSH receptor) observed lower apoptosis rate (measured by 7‐amino‐actinomycin incorporation by apoptotic cells) in follicles from women over 35 years compared to younger ones. The apoptosis rate was also lower in women over 40 years with diminished ovarian reserve compared to a group of the same age with normal ovarian reserve (Regan et al, ). On possible interpretation of these conflicting observations is that cumulus cell apoptosis would increase with advanced age (Lee et al, ) whilst mural CGs apoptosis paradoxically decreases due to a slower turnover of this cell population (Regan et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…However, a recent flow cytometry study with selective gating of pure mural GCs (identified by the expression of FSH receptor) observed lower apoptosis rate (measured by 7‐amino‐actinomycin incorporation by apoptotic cells) in follicles from women over 35 years compared to younger ones. The apoptosis rate was also lower in women over 40 years with diminished ovarian reserve compared to a group of the same age with normal ovarian reserve (Regan et al, ). On possible interpretation of these conflicting observations is that cumulus cell apoptosis would increase with advanced age (Lee et al, ) whilst mural CGs apoptosis paradoxically decreases due to a slower turnover of this cell population (Regan et al, ).…”
Section: Resultsmentioning
confidence: 99%
“…In addition, granulosa cell apoptosis increases dramatically around the time of dominant follicle selection when the ratio of androgen is greater than estrogen ( 49 , 57 59 ). The start of follicle selection coincides with the down-regulation of granulosa cell BMPR1B and FSHR expression ( 3 , 4 , 9 ).…”
Section: Regulation Of Bmpr1b and Fshr And Their Influence On Apoptosmentioning
confidence: 99%
“…The follicles with granulosa cells expressing LHRs are able to continue to produce estrogens, and are recruited into the dominant cohort. FSHR is protective against apoptosis; therefore, as the FSHR level falls, apoptosis increases ( 4 ).…”
Section: Regulation Of Bmpr1b and Fshr And Their Influence On Apoptosmentioning
confidence: 99%
See 1 more Smart Citation
“…Such topographicanatomical peculiarities can be considered standard for the fetuses of the given age group. Though they can be indicative of developmental retardation at the late stages of the perinatal development, which is not mentioned in the works of certain researchers [9,14,16,19,23,25].…”
Section: Discussionmentioning
confidence: 98%